2001
DOI: 10.1007/s005920170016
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperglycemia and acute hyperinsulinemia decrease plasma fibrinolytic activity and increase plasminogen activator inhibitor type 1 in the rat

Abstract: Decreased plasma fibrinolysis may contribute to accelerated atherothrombosis in diabetes. To observe whether hyperglycemia and hyperinsulinemia, common findings in type 2 diabetes, acutely affect plasma fibrinolysis in vivo, we evaluated plasma fibrinolysis (lysis of fibrin plates, free PAI-1 activity and t-PA activity) in the rat after a hyperglycemic euinsulinemic clamp (n=8), an euglycemic hyperinsulinemic clamp (n=7) or a saline infusion (n=15). Plasma fibrinolytic activity was sharply reduced after both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 30 publications
3
70
1
2
Order By: Relevance
“…18 Postulated mechanisms for this association include that hyperglycemia may be related to atherosclerotic disease or to an antifibrinolytic effect. 19 In contrast, our results demonstrated that hyperglycemia was not related to the reperfusion rate after MT. This result is in line with a recent study reporting the lack of an association between vessel recanalization and diabetes mellitus or glucose levels in patients receiving diverse AF indicates atrial fibrillation; CI, confidence interval; ICH, intracerebral hemorrhage; mRS, modified Rankin Scale; NIHSS, National Institutes of Health Stroke Scale; OR, odds ratio; PH, parenchymal hematoma type 2; SICH, symptomatic intracranial haemorrhage; and TIMI, Thrombolysis In Myocardial Ischemia scale.…”
Section: Kim Et Al Impact Of Glucose On Outcomes In the Swift Study 123contrasting
confidence: 81%
“…18 Postulated mechanisms for this association include that hyperglycemia may be related to atherosclerotic disease or to an antifibrinolytic effect. 19 In contrast, our results demonstrated that hyperglycemia was not related to the reperfusion rate after MT. This result is in line with a recent study reporting the lack of an association between vessel recanalization and diabetes mellitus or glucose levels in patients receiving diverse AF indicates atrial fibrillation; CI, confidence interval; ICH, intracerebral hemorrhage; mRS, modified Rankin Scale; NIHSS, National Institutes of Health Stroke Scale; OR, odds ratio; PH, parenchymal hematoma type 2; SICH, symptomatic intracranial haemorrhage; and TIMI, Thrombolysis In Myocardial Ischemia scale.…”
Section: Kim Et Al Impact Of Glucose On Outcomes In the Swift Study 123contrasting
confidence: 81%
“…PAI-1 levels are elevated in patients with diabetes mellitus and coronary artery disease [2,21] and are associated with an enhanced risk of coronary events [10,12]. Besides its effects on TF and TFPI, guggulsterone downregulated PAI-1 expression both in quiescent and TNF-a stimulated cells; hence, guggulsterone may be particularly beneficial in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, further activation of NF-B-dependent transcription was observed with proinflammatory cytokines (IL-1 , TNF-), raising the possibility that NF-B may play a pivotal role in the integration of multiple risk factors seen in the metabolic syndrome. Recent clinical data clearly show that the constellation of risk factors such as hyperglycemia, hyperinsulinemia, and high plasma cytokine levels produces an increase in plasma PAI-1 and fibrinogen, causing enhanced coagulability and impaired fibrinolysis, with 10 resultant increase in the risk of cardiovascular events (Schneider, Nordt, & Sobel, 1993;Pandolfi et al, 2001). Our data also show the increased promoter activity of fibrinogen and PAI-1 genes by glucose, in accordance with the increased plasma level of these proteins and hypercoagulability in patients with uncontrolled diabetes (Bruno et al, 1996;Festa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%